The perceptions of Bachelor of Library and Information Science Students of the University of the Philippines Diliman on the Master of Library and Information Science Program - Nacional, Sotero T. III (1998)
This research focused on the perceptions of 60 UP-BLIS students on the Master of Library and Information Science Program, with the purpose of improving the student's view of the MLIS program, as well as advancing the program itself. The study sought to: 1) find out how UP-BLIS perceive the MLIS program and if they think it is worth pursuing after graduation; 2) determine the level of familiarity of BLIS students regarding the MLIS program; 3) find out if they would pursue the program after graduation; 4) determine the reasons for pursuing the program; 5) determine the reasons for not pursuing the program; 6) determine the factors that affect the perceptions of UP-BLIS students to pursue or not to pursue the MLIS program; and 7) indicate the expectations of BLIS students if they would pursue it.